Apelin protects against NMDA-induced retinal neuronal death via an APJ receptor by activating Akt and ERK1/2, and suppressing TNF-α expression in mice - Yuki Ishimaru; Akihide Sumino; Daiki Kajioka; Fumiya Shibagaki; Akiko Yamamuro; Yasuhiro Yoshioka; Sadaaki Maeda (Elsevier, 2017)
Glutamate excitotoxicity mediated by N-methyl-d-aspartate (NMDA) receptors is an important cause of retinal ganglion cell death in glaucoma. To elucidate whether apelin protects against retinal neuronal cell death, we examined protective effects of exogenous and endogenous apelin on neuronal cell death induced by intravitreal injection of NMDA in the retinas of mice. An intravitreal injection of NMDA induced neuronal cell death in both the retinal ganglion cell layer and inner nuclear layer, and reduced the amplitudes of scotopic threshold response (STR) in electroretinography studies. Both cell death and STR amplitudes decrease induced by NMDA were prevented by a co-injection of [Pyr1]-apelin-13, and were facilitated by apelin deficiency. The neuroprotective effects of [Pyr1]-apelin-13 were blocked by an apelin receptor APJ antagonist, and by inhibitors of Akt and extracellular signal-regulated kinase 1/2 signaling pathways. Additionally, an intravitreal injection of tumor necrosis factor-α (TNF-α) neutralizing antibody prevented NMDA-induced retinal neuronal cell death, and exogenous and endogenous apelin suppressed NMDA-induced upregulation of TNF-α in the retina. These results suggest that apelin protects neuronal cells against NMDA-induced death via an APJ receptor in the retina, and that apelin may have beneficial effects in the treatment of glaucoma.